Research on the ultrathin structure of cells of different distillers’ yeast races and its dependence on the concentration of dry matter in wort. - Mudrak, Tatiana; Kovalchuk, Svitlana; Kuts, Anatoly; Dotsenko, Viktor (My University, 2020)
There are a number of directions of introducing the resource-saving and energy-efficient technology of alcohol washes into alcohol production. One of them is the use of highly concentrated wort from grain raw materials. Application of highly productive strains of distillers’ yeast is the basis of resource-saving and energy-efficient technologies, a way to reduce the cost of ethanol and increase the profitability of its production. To develop the technology of highly concentrated wash from grain raw materials, it is necessary to select the appropriate yeast races and study their morphological and physiological properties. Diagnostics of the physiological state of microorganisms has been performed. It has been studied how the concentration of dry matter in the wort effects on the specific morphological and cytological features of the structure of yeast cells (distillers’ yeast S. cerevisiae, races DO-16, DO-11, K-81, XII) when they are cultured on media from starch-containing raw materials. The concentration of dry matter in the wort was 20 and 28%. It has been found that the S. cerevisiaerace DO-16 bred by selection synthesises the largest number of yeast cells when the dry matter concentration is 28%. The osmophilic S. cerevisiae races DO-16 and DO-11 had smaller sizes and areas of their cells in comparison with the thermotolerant and mesophilic races of S. cerevisiaeK-81 and XII at the 28% concentration of DM in the wort. During fermentation, these parameters characterise the increase in the working surface of the yeast in the medium fermented. This allows accelerating the fermentation process and ensuring microbiological purity of the medium, which is especially important for highly concentrated wort. The morphological and cytological studies of the S. cerevisiaerace DO-16 have proved its advantages over the races DO-11, K-81, XII in fermenting highly concentrated wort. The studies of the intracellular structure of the yeast S.cerevisiaeDO-16, DO-11, K-81, XII have allowed establishing the relationship between the formation of glycogen in yeast cells and the DM concentration of the wort. When culturing industrial yeast at the DM concentration 28%, the glycogen content in the cells ofS. cerevisiaeDO-16 was significantly higher compared with the races under study. This indicates that these conditions of the culture medium are favourable for this race.
Keywords: distillers’yeasts; ultrathin structure; highly concentrated wort; dry matte; fermentation; culturing; спиртові дріжджі; ультратонка структура; висококонцентроване сусло; сухі речовини; культивування; кафедра готельно-ресторанної справи; кафедра біотехнології продуктів бродіння і виноробства